Uso de antipsicóticos em crianças e adolescentes - Claudia Santos Oliveira Hartmann; Sergio Antonio Antoniuk; Giovani Ceron Hartmann; André Luis Santos do Carmo (Sociedade Brasileira de Pediatria, 2022)
OBJECTIVE: To describe the profile of pediatric patients undergoing regular treatment with antipsychotics agents. METHODS: Descriptive study of a case series with cross-sectional data collection of patients' files using antipsychotics agents, under 14 years of age treated at a Neuropediatric service from April to July 2020. For statistical analysis, we used the Fisher exact test and the Pearson's Chi-square test with a 5% significance level. RESULTS: We assessed 98 patients, and 74 (75.5%) were males, the median age in the evaluation period was 8.5 (2.5 to 14 years). The main diagnosis was Autism Spectrum Disorder (53%) and Intellectual Deficit (46.9%). The most frequent prescription indications were aggressiveness (76.5%) and restlessness (43.8%). The main drugs prescribed were Risperidone (85.7%) and Periciazine (6.1%). The most evident adverse effects were weight gain (15.3%) and increased appetite (10.2%). The MOAS (Modified Overt Aggression Scale) showed changes in 71 patients (72.4%). Clinical evolution was reported as favorable by parents for 95 patients (96.94%). CONCLUSIONS: The use of antipsychotics in pediatrics is constantly expanding, but studies on the effects on this population are still lacking and with that the off-label use becomes commonplace. Further studies on the use of antipsychotics in the pediatric age group are expected to be developed.